IN SEARCH OF FAIR UNIT RATE TERMINAL NAVIGATION CHARGE FOR SOEKARNO HATTA AIRPORT & HALIM AIRPORT USING ACTIVITY BASED COSTING SYSTEM AT AIRNAV INDONESIA - Ahmad Junaedi, Rahayu
Current Air Navigation Charge system does not fully apply the concept of cost recovery that become the main base of financial management in AirNav Indonesia according to President Decree No 77 of 2012. One of the proofs is that the Terminal Navigation Charge structure is based on three categories: Precision, Non-Precision, and Information.